Fatigue analysis for the aluminum alloy 7050-T7451 performed by a two scale continuum damage mechanics model. (February 2020) - Araújo, L.M.; Ferreira, G.V.; Neves, R.S.; Malcher, L.
Highlights: Fatigue life estimate by continuum damage. Stress triaxiality and normalized third invariant effects in damage evolution law. Two scale model in high cyclic fatigue. Alternative methodology of fatigue life estimate. Abstract: The aim of this work is propose a fatigue life prediction tool, regarding a two scale elastic (macro)/elastoplastic (micro) model and validate the application of the incremental damage, based on the improved Continuum Damage Mechanics (CDM) evolution law, for tests performed in cyclic force control, taken from the literature. In this setting, a localization law is assumed to perform the transition between the macro and the micro strain fields, and the incremental damage is coupled into the microscale behavior of the material, in order to detect the degradation, according to the number of cycle applied at the crack initiation, for the aluminum alloy 7050-T7451. Furthermore, the improved CDM model is also employed to demonstrate the effect of the calibration point in the fatigue analysis and to refine the life estimate. The numerical results are compared with traditional Lemaitre incremental damage and with the well-established Smith-Watson-Topper criterion, in order to show that the developed method is a promising alternative fatigue tool. The results have described adequately the fatigue behavior of the alloy, regarding tension/compression, fully reverse torsional and biaxial proportional loading, allowing a proportion of 87, 6% within the band width 4, which is a satisfactory result for an alloy with a complex fatigue behavior, such as the 7050-T7451, and it is close to the proportion predicted by the SWT criterion.